Sources of vitamin D and calcium in the diets of preschool children in the UK and the theoretical effect of food fortification. Issue 6 (3rd October 2014) - Cribb, V. L.; Northstone, K.; Hopkins, D.; Emmett, P. M.
Abstract: Background: Dietary intakes of vitamin D are very low in the UK. Dietary calcium is also necessary to promote bone health. The fortification of foods with vitamin D could be a safe and effective way of increasing intake. Methods: Diets of preschool children, 755 at 18 months and 3.5 years, from the Avon Longitudinal Study of Parents and Children were assessed using dietary records completed by parents. Energy, vitamin D and calcium intakes were calculated. Multinomial logistic regression was used to estimate the odds ratio for being in the highest/lowest quartile of intake. Intakes were recalculated to test different fortification regimes. Results: Vitamin D intakes were low; all children were below the UK and US dietary recommendations. Calcium intakes decreased between the two ages as a result of reduced milk consumption. Children in the lowest quartile for vitamin D intake at 18 months were twice as likely to remain in that quartile at 3.5 years (odds ratio = 2.35; 95% confidence interval = 1.56–3.55). The majority of foods provide no vitamin D with fat spreads and milk as the main sources. The contribution from breakfast cereals increased, from 6% to 12%, as a result of the increased consumption of fortified cereals. Dairy foods provided the highest contribution to calcium at 18 months but were less important at 3.5 years. Theoretical intakes from different fortification regimens suggest that milk fortified at 2 μg 100 g –1 vitamin D would provide most children with adequate but not excessive intakes. Conclusions: Dietary vitamin D intakes were very low and calcium intakes were mostly adequate. Fortification of milk with vitamin D could be a good way to boost intakes.